2004
DOI: 10.1242/dev.01066
|View full text |Cite
|
Sign up to set email alerts
|

Specification of the otic placode depends on Sox9 function inXenopus

Abstract: The vertebrate inner ear develops from a thickening of the embryonic ectoderm, adjacent to the hindbrain, known as the otic placode. All components of the inner ear derive from the embryonic otic placode. Sox proteins form a large class of transcriptional regulators implicated in the control of a variety of developmental processes. One member of this family, Sox9, is expressed in the developing inner ear, but little is known about the early function of Sox9 in this tissue. We report the functional analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 68 publications
3
79
0
1
Order By: Relevance
“…The formation of empty otocysts devoid of sensory organs suggests that the formation of the nonsensory portion of the otocyst (the membranous labyrinth) may be uncoupled from that of the sensory organs. This finding is consistent with recent studies that separate the roles of genes involved in otic placode specification from those involved in later patterning (Groves and Bronner-Fraser, 2000;Saint-Germain et al, 2004;Kil et al, 2005). By otocyst stages, we found a complete lack of regeneration after ablation.…”
Section: Complete Ablationsupporting
confidence: 93%
See 1 more Smart Citation
“…The formation of empty otocysts devoid of sensory organs suggests that the formation of the nonsensory portion of the otocyst (the membranous labyrinth) may be uncoupled from that of the sensory organs. This finding is consistent with recent studies that separate the roles of genes involved in otic placode specification from those involved in later patterning (Groves and Bronner-Fraser, 2000;Saint-Germain et al, 2004;Kil et al, 2005). By otocyst stages, we found a complete lack of regeneration after ablation.…”
Section: Complete Ablationsupporting
confidence: 93%
“…As a probe, we used the Xenopus homeobox gene Distalless 3 (X-dll3; actually Dlx5; Stock et al, 1996), which is strongly and globally expressed in the otic placode and otocyst (Papalopulu and Kintner, 1993). We have found that X-dll3 is expressed in prospective otic regions well before placode formation (stage 13, which is just after gastrulation), making it one of the earliest otic genes expressed in Xenopus, although not earlier than the transcription factors Sox9 and Pax8 (Saint-Germain et al, 2004). These ablations were done until 100% of labeled embryos were completely missing their inner ears on the operated side, indicating that the experimenter had achieved proficiency.…”
Section: Experimental Manipulation Of Otic Tissuementioning
confidence: 95%
“…In these cases, it was not clear whether the inhibition of cartilage development resulted from the failure of the mesenchyme to form cartilage precursor cells or from the resorption of initiated cartilage. In our previous study, we had found that abrogation of Smad4 in chondrocytes resulted in dwarfism with a severely disorganized growth plate characterized by an expanded resting zone of chondrocytes, reduced chondrocyte proliferation, and accelerated hypertrophic differentiation (Saint-Germain et al, 2004). Therefore Smad4-mediated BMP4 signals inhibit chondrocyte hypertrophic differentiation.…”
Section: Conditional Knockout Affects Osseous Development In the Cochmentioning
confidence: 97%
“…Normally, BMPs act during early bone development and regulate the shape of mesenchymal condensation. They are involved in mesoderm induction and bone shape determination during bone development (Saint-Germain et al, 2004;Tsumaki and Yoshikawa, 2005). Chang et al (2002) compared the phenotypes of the otic capsule in ears that were infected with an avian retrovirus encoding either constitutively active or dominant-negative forms of the Bmp type IB receptor (Bmpr1b).…”
Section: Conditional Knockout Affects Osseous Development In the Cochmentioning
confidence: 99%
“…In zebrafish, wnt signalling has been proposed to play a role in otic placode induction, by regulating expression of Fgf3 and Fgf8 in the hindbrain. Furthermore, injection of Wnt antagonists (GSK3b; Saint-Germain et al, 2004) and Wnt8 morpholino oligos (Phillips et al, 2004) resulted in otic vesicles of reduced size. Therefore, Tcf/Lef proteins play a positive role in the proposed pathway, the phenotypic consequences for Tle/Aes misexpression nevertheless would be contradictory to our results.…”
Section: Groucho/tle Proteins Strongly Affect Otic Vesicle Developmentmentioning
confidence: 99%